Penerapan Algoritma Welch Powell Untuk Menyusun Jadwal Mata Kuliah Di IST Annuqayah - Inda Arundani; Luluk Sarifah; Fiqih Rahman Hartiansyah (Alpha-Epsilon: Journal of Mathematics, 2025)
Graph coloring is the giving of color to certain objects in the graph. These objects can be nodes, edges, and regions. This study aims to look at the process and results of graph coloring using the Welch Powell Algorithm in the preparation of class schedules for the Mathematics and Biology Study Program, Faculty of Mathematics and Natural Sciences, Annuqayah Institute of Science and Technology. The type of research used is descriptive qualitative research. The object of research in this study is the list of lecturers, list of courses, lecture active hours, and the number of rooms used. Data analysis was carried out by modeling a list of lecturers with a list of courses into a graph and determining the minimum color in the coloring process using Welch Powell's algorithm. In this research, we know the performance of the Welch Powell algorithm in compiling schedules for each study program and combined scheduling. Based on the scheduling results, it can be concluded that the application of Welch Powell's algorithm for combined scheduling is more effective and more efficient to use than scheduling for each study program. In addition to not overlapping between courses, it can also save space.